Estimated climate impact of replacing agriculture as the primary food production system - MacDougall,AH; Rogelj,J; Withey,P (Environmental Research Letters, 2021)
Global agriculture is the second largest contributor to anthropogenic climate change after the burning of fossil fuels. However the potential to mitigate the agricultural climate change contribution is limited and must account for the imperative to supply food for the global population. Advances in microbial biomass cultivation technology have recently opened a pathway to growing substantial amounts of food for humans or livestock on a small fraction of the land presently used for agriculture. Here we investigate the potential climate change impacts of the end of agriculture as the primary human food production system. We find that replacing agricultural primary production with electrically powered microbial primary production before a low-carbon energy transition has been completed could redirect renewable energy away from replacing fossil fuels, potentially leading to higher total CO2 emissions. If deployed after a transition to renewable energy, the technology could alleviate agriculturally driven climate change. These diverging pathways originate from the reversibility of agricultural driven global warming and the irreversibility of fossil-fuel CO2 driven warming. The range of reduced warming from the replacement of agriculture ranges from −0.22 (−0.29 to −0.04) C for shared socioeconomic pathway (SSP)1 −1.9 to −0.85 (−0.99 to −0.39) C for SSP4-6.0. For limited temperature target overshoot scenarios, replacement of agriculture could eliminate or reduce the need for active atmospheric CO2 removal to achieve the necessary peak and decline in global warming.